An Analysis of Gestures Found in "A Quiet Place" Film - Rahma Amalia Putri; Siti Lestari; AB Prabowo KA (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2020)
This fnal project presents the analysis of gestures found in “A Quiet Place” flm. Themain purposes of this research are (1) to fnd out the kinds of gestures found in “AQuiet Place” flm (2) to analyze the function of gesture found in “A Quiet Place” Film.The method of this research is descriptive qualitative research. For collecting the data,the researcher should watch “A Quiet Place” Film. After watching flm, the researchershould fnd out the kinds of gesture in another journal or books then analyzing thekinds of gesture that found in “A Quiet Place” flm. The researcher found the kinds ofgesture that written by David McNeill and Levy 2005. There are four dimensions of theprevious researcher about the kinds of gesture: Iconic, Metaphoric, Deictic, and Beats.That are the kinds of gesture that the researcher will analyze based on the flm. The fourkinds of gesture is importance for balancing the speakers meaning when they talk, andwhen the speakers did not allow to speech or using their sounds. Study about gesture isimportant, as a student of English education the researcher took this subject because itrelated to cultural understanding and linguistics. The researcher chose “A Quiet Place”flm that relating to this research. “A Quiet Place” is an American post-apocalyptic horrorflm directed by John Krasinski in 2018, who wrote the screenplay with Bryan Woods andScott Beck. The flm stars Krasinski, alongside Emily Blunt, Millicent Simmonds, andNoah Jupe. The plot revolves around a family struggling to survive in a post-apocalypticworld inhabited by blind extraterrestrial creatures with an acute sense of hearing. A QuietPlace premiered at South by Southwest on March 9, 2018, and was released in the UnitedStates on April 6, 2018, by Paramount Pictures. This is one of the flm which is not havingany conversations. The characters are used gestures for communication. The researchersuggested the readers to be more understanding about gesture, and also the researchersuggested the future researcher that another drama or flm could be selected to nextresearcher and they could explain more about this subject because the gestures is notonly about non-verbal communication, it is related to another theory of body language.